A PASSAGEM DO BASTÃO PARA HERDEIRAS: O CASO DE UMA EMPRESA DO ABC PAULISTA EM FASE DE PREPARAÇÃO PARA A SUCESSÃO FAMILIAR - Eloi, Cristiany Bim Gurati (2014)
First objective of this study is to contribute to the specialized debate and its effort to point out ways to help family business ensuring continuityfrom the secondgeneration of leaders. Although inaccurate andoutdated, statistics show 70 por cento of family business succumbing before reachingthe second generationand, on average, only 15% survive tothe third generation. Successionis the most focused subjectforexperts. However, there are indications, although studiesmultiplyevery year, there is a relativestagnation in thetheoreticalfield. During the last yearsthere has been aslight increase inparticipation ofwomenin positions of family businesses CEO which, historically,influenced bypatriarchal culture, elect theirheirsas successors. This study, therefore, was guided by the general objective of identifying elements of the succession process that will allow a deeper understand of the apparent shift that is occurring in family businesses, evidenced by theslight increase in thecontroltransfer to women, which, in principle, contraries thepatriarchal tradition. Specifically, this study was guidedby the following objectives: i)examinethe practicesof a businessfamily that having openedthe succession processin their own company, is in preparationfora daughterto take overthe business in place of the father/founder; ii) under the light of the accumulated theoretical knowledge and practices of this business family, gather knowledge that will enable the formulation of hypothesis(s) that may contribute to the probation of the problems treated in this study. This isanexploratory researchthat employsthe followingmethods: qualitativemonographic/case study anddialectical. The unit of analysisisafamily ownedcompany basedin the ABCPaulistaregionfor 30 yearswhichis in processof preparing theheiress to take commandin placeof the father/founder. Evidences show that the succession decision was strategically made in order to ensure that the family estate remains controlled by the founder, as professed by the patriarchal patrimonialism model deep-rooted in Brazilian society.